Molecular and serological prevalence of Babesia bovis and Babesia bigemina in water buffaloes in the north region of Brazil - Da Silva, Jenevaldo Barbosa [UNESP]; André, Marcos Rogério [UNESP]; da Fonseca, Adivaldo Henrique; de Albuquerque Lopes, Cinthia Távora; da Silva Lima, Danillo Henrique; de Andrade, Stefano Juliano Tavares; Oliveira, Carlos Magno Chaves; Barbosa, José Diomedes (Elsevier, 2013)
Bovine babesiosis is a tick-borne disease caused mainly by Babesia bovis and Babesia bigemina, which are associated to considerable economic losses in cattle herds worldwide. Approximately 60% of buffalo herds in South America are located in Northern Brazil. Little is known about the impact of babesiosis on buffalo herds in Brazil. The present work aimed to verify the occurrence of B. bovis and B. bigemina in 542 water buffaloes in the state of Pará, Northern Brazil, using molecular and serological techniques. The percentage of seropositive animals for B. bovis and B. bigemina was 41.2% and 19.0%, respectively, by ELISA. B. bovis and B. bigemina DNA were detected in 15 and 16% of sampled buffaloes, respectively. A high correlation (Kappa index of 0.9) between serological and molecular tests suggests that the combination of the utilized techniques in the present study is suitable for babesiosis diagnosis in an endemic unstable area. Significantly difference of positivity for serological and molecular assays was verified to localities and reproductive status of sampled animals, but not between buffalo breeds. The immune status of sampled buffaloes associated to the circulation of babesiosis agents in sampled population suggests that the studied area is at risk to clinical babesiosis outbreaks. Furthermore, this study demonstrated that this region can be classified as endemically unstable. © 2013 Elsevier B.V.
Keywords: Babesia; Brazil; ELISA; NPCR; Water buffaloes